Provenance and Annotation of Data and Processes 6th International Provenance and Annotation Workshop, IPAW 2016, McLean, VA, USA, June 7-8, 2016, Proceedings - Mattoso, Marta; Glavic, Boris (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the refereed proceedings of the 6th International Provenance and Annotation Workshop, IPAW 2016, held in McLean, VA, USA, in June 2016. The 12 revised full papers, 14 poster papers, and 2 demonstration papers presented were carefully reviewed and selected from 54 submissions. The papers feature state-of-the-art research and practice around the automatic capture, representation, and use of provenance. They are organized in topical sections on provenance capture, provenance analysis and visualization, and provenance models and applications.